Ki tō ringa ki ngā rākau ā te Pākehā? Drawings and Signatures of Moko by Māori in the Early 19th Century - Ellis, Ngārino (Waka Kuaka, 2014)
Self-portraits using moko have a relatively short history (1815-1884) within Māori culture, yet they provide many revelations about Māori and how they saw themselves. These took two forms: those which were made on land deeds across the country, and those made on request for Europeans. Examples range from a letter to King William IV in 1831 signed by 13 Ngapuhi chiefs, to a self-portrait by Te Peehi Kupe of Ngāti Toa Rangitira made in Liverpool, England and two drawings by Tuai of his Ngāre Raumati brother Korokoro. I argue here that these drawings should be read as part of a unique system of Māori self-portraiture in which the physiognomic details so critical in Western European traditions of self-portraiture are replaced by complex forms of moko. In doing so, they provide a snapshot into cross-cultural engagement and interaction between Māori and Pākehā, and suggest a deeper level of Māori understanding of such practices than previously thought. That these drawings are regarded as the ancestors by their descendants today is evidence of the enduring power of these tohu.